Comprehensive heterocyclic chemistry III - Katritzky, Alan R.; Ramsden, Christopher A., 1946-; Scriven, Eric F. V.; Taylor, Richard J. K. (Elsevier, 2008)
Provides the first point of entry to the literature for all scientists interested in heterocyclic ring systems.